1994
DOI: 10.1111/j.1464-410x.1994.tb07604.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in pTa‐pT1 superficial bladder tumours treated with intravesical instillations

Abstract: Prognostic factor analysis, as an auxiliary study of trials of patients treated for superficial bladder tumours, is mandatory. The prognostic factors related to recurrence-free interval found in this study, location of the tumour and multiplicity, may be of use in the stratification necessary for current protocol design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
21
1
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 13 publications
9
21
1
4
Order By: Relevance
“…In our study, the grade does not appear as an independent prognosis variable. In this aspect, our results are consistent with those included in other multivariate studies, in terms of survival, 6,12,19,21 recurrence, 8,11,[15][16][17][18][19]25 and progression. [21][22][23]25 Our study shows that there are several significant variables in the prognosis of bladder TCC at T1 and T2a classifications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the grade does not appear as an independent prognosis variable. In this aspect, our results are consistent with those included in other multivariate studies, in terms of survival, 6,12,19,21 recurrence, 8,11,[15][16][17][18][19]25 and progression. [21][22][23]25 Our study shows that there are several significant variables in the prognosis of bladder TCC at T1 and T2a classifications.…”
Section: Discussionsupporting
confidence: 92%
“…14 Our study shows that the risk of recurrence in multiple tumors is almost three times greater than that of single tumors, making tumor multifocality the main factor determining the risk of recurrence. Research by Allard et al, 9 Witjes et al, 15 Parmar et al, 16 and Mulders et al, 17 has shown the independence of tumor multifocality and highlight the vital role this variable plays in tumor recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have demonstrated the prophylactic efficacy of intravesical chemotherapy to these high-risk tumors, which was assumed to result from alterations in the biologic behavior of the tumors. 24,25,30 However, our results were not enough to show the effectiveness of low-dose epirubicin in the treatment of high-risk tumors because our study was neither randomized nor controlled and the number of patients examined was too small. Moreover, the ability of epirubicin to prevent progression remains unclear.…”
Section: Discussionmentioning
confidence: 80%
“…2,27 However, this factor was not prognostic for some intravesical adjuvant therapies. 12,14,25 This may be attributed to the ability of intravesical chemotherapy to suppress the high potential for recurrence of large tumors. On the basis of our results, tumor size possesses a significant predictive value, suggesting that our low-dose epirubicin does not alter the risk of recurrence for large tumors.…”
Section: Discussionmentioning
confidence: 99%
“…El análisis descriptivo de ambas series revela que el porcentajes de recidiva en ambas centros (48.8% y 56.6%) es similar al de otras series históricas publicadas [10][11][12][13][14][15][16], sin embargo el porcentaje de progresión es menor que en otros estudios [1, 14,[16][17][18] Los factores pronósticos para una primera recidiva son equivalentes al de otras series e incluyen la edad, grado, número y tamaño tumoral junto con el tratamiento. Tanto la presencia de cis como el estadio tumoral, no fueron significativos para la recidiva tumoral [17].…”
Section: Discussionunclassified